Pengaruh Kepuasan Wajib Pajak Terhadap Kwalitas Pelayanan dan Kepatuhan Wajib Pajak pada KPP di Tanjung Karang - . Yuliana (Jurnal Akuntansi dan Keuangan, 2016)
Taxes are a source of regional income used for capital expenditures of which is for the construction or repair of roads. However Diijen Rahmany Tax (2011) recognizes the Indonesian tax revenue ratio is still low when compared with the ratio of tax revenue neighboring countries. Even in terms of compliance to pay taxes, the Indonesian people, including low. This study aims to observe the effect of obligatory feed satisfaction and quality of service on tax compliance. on STO Cape Coral. The data used in this study are primary data is done by distributing questionnaires and interviews directly with the parties related to the research conducted, in this case the taxpayer. Besides using secondary data because the researchers collected information from data that has been processed the KPP, which taxes satisfaction data. Based on the results of the study concluded that 1) the taxpayer satisfaction affects the quality of service .2) Quality of care affect the taxpayer compliance.